2012
DOI: 10.1002/chem.201200111
|View full text |Cite
|
Sign up to set email alerts
|

A Functionally Selective Synthetic Mimic of the HIV‐1 Co‐receptor CXCR4

Abstract: Small and selective: A synthetically assembled CXCR4 mimetic peptide, which presents the three extracellular loops (ECLs) of this HIV‐1 co‐receptor, is able to discriminate between gp120 from X4‐ and R5‐tropic HIV‐1 in binding assays involving recombinant proteins, as well as in cellular infection assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…ECL2 of CXCR4 and the N-terminus of CCR5 are indeed major gp120 binding determinants at the coreceptor surface and we have recently shown that peptides derived from ECL2-X4 (176-202) have antiviral properties against X4-strain NL4.3 (IC 50 ¼ 9.3 AE 0.3 mmol/l) (Fig. 1b) [30][31][32][33][34][35][36][37]. These results are consistent with reporting of CCR5 surface mimicry by gp120 specific antibodies CDRs [38,39].…”
mentioning
confidence: 99%
“…ECL2 of CXCR4 and the N-terminus of CCR5 are indeed major gp120 binding determinants at the coreceptor surface and we have recently shown that peptides derived from ECL2-X4 (176-202) have antiviral properties against X4-strain NL4.3 (IC 50 ¼ 9.3 AE 0.3 mmol/l) (Fig. 1b) [30][31][32][33][34][35][36][37]. These results are consistent with reporting of CCR5 surface mimicry by gp120 specific antibodies CDRs [38,39].…”
mentioning
confidence: 99%
“…We could select an entry inhibitory peptide (XD3) with remarkable homology to the N-terminus of CCR5 and CXCR4 by phage display using CD4i epitopes on native dualtropic Env as target [77]. For CXCR4, which is less dependent on its N-terminus for HIV entry, we further designed a peptide comprising ECL1 to 3 linked to short spacers, which showed selective CXCR4 binding and entry inhibition in the low micromolar range [78].…”
Section: Hiv-1 Coreceptors Ccr5 and Cxcr4 And Inhibitors Of Coreceptomentioning
confidence: 99%
“…Peptides were synthesized using Fmoc/t-Bu based solid phase peptide synthesis as previously described for CX4-M1 13,14 . Briefly, peptides were generated as C-terminal amides, and the N-terminus was acetylated.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…This peptide, which presents the three ECLs of CXCR4, was found to selectively bind to HIV-1 gp120 from X4 tropic virus strains 13 , as well as to peptides presenting the V3-loop of these gp120 proteins 14 , which is part of the corecetor binding site of gp120 15 . Furthermore, CX4-M1 selectively inhibits infection of cells with X4-tropic HIV-1 13 . We now asked the question whether this functional selectivity of CX4-M1 is also present in its interaction with the natural ligand of CXCR4, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation